KETELADANAN KEPEMIMPINAN YESUS DAN IMPLIKASINYA BAGI KEPEMIMPINAN GEREJA PADA MASA KINI - K Katarina; Krido Siswanto (Sekolah Tinggi Teologi Simpson, 2018)
Katarina & Krido Siswanto, Exemplary Leadership of Jesus and Its Implications for Church Leadership In Today. This paper is an analysis of the exemplary leadership of Jesus and its implications in the present. The author conducts literature research by looking at the principles of Jesus' leadership in the four Gospels, then finding the implications. From the results of the study, the Bible shows that Jesus is a figure who can be an example to his community and the example of his leadership is still relevant to Christian leadership today. The Bible shows that there are at least four areas of exemplary leadership of Jesus: the character of Jesus in leading, the spirituality of Jesus in leading, the management of Jesus in leading, and the ministry of Jesus in leading. Katarina & Krido Siswanto, Keteladanan Kepemimpinan Yesus dan Implikasinya Bagi Kepemimpinan Gereja Pada Masa Kini. Tulisan ini merupakan analisis tentang keteladanan kepemimpinan Yesus dan implikasinya pada masa kini. Penulis melakukan penelitian literatur dengan mencermati prinsip kepemimpinan Yesus dalam keempat Injil, kemudian menemukan implikasinya. Dari hasil penelitian, Alkitab menunjukkan bahwa Yesus adalah sosok yang dapat menjadi teladan bagi komunitas-Nya dan keteladanan kepemimpinan-Nya masih relevan dengan kepemimpinan Kristen pada masa kini. Alkitab menunjukkan paling tidak ada empat bidang keteladanan kepemimpinan Yesus, yaitu: karakter Yesus dalam memimpin, kerohanian Yesus dalam memimpin, manajemen Yesus dalam memimpin, dan pelayanan Yesus dalam memimpin.